An Analytical Observational Study to Determine the Antibacterial and Antioxidant Properties of Dashapushpam, Ten Medicinal Plants - Praseetha, P.K; Sreedevy, K (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
A collection of ten revered herbs known with their traditional and therapeutic significance is known as Dashapushpam in the Kerala state of India, and particularly utilized by Keralites on the onsets of the monsoons. The current research aims to showcase the antibacterial and antioxidant properties of these ten herbs. The antibacterial efficacy was assessed against Gram-negative Escherichia coli and Gram-positive Bacillus subtilis using the agar-gel diffusion method. All extracts exhibited varying degrees of activity against these test organisms, with their effectiveness compared to the standard antibiotic amoxicillin. Additionally, the study evaluated the antioxidant potential of the Dashapushpam herbs through the nitric oxide scavenging assay, revealing different levels of antioxidant activity among the plants. These findings support the potential use of these ten herbs in medicinal applications as anti-infective agents.